Direct synthesis of porous graphitic carbon sheets grafted on carbon fibers for high-performance supercapacitors. Issue 7 (25th January 2019) - Zhang, Xiaohua; Li, Hengxiang; Qin, Bing; Wang, Qun; Xing, Xiaohan; Yang, Donghua; Jin, Li'e; Cao, Qing
Abstract : Porous graphitic carbon sheets grafted on microfibers were synthesized with the aid of a green activating–graphitizing agent K3 [Fe(C2 O4 )3 ]. Abstract : Biomass-derived carbon with a high specific surface area, appropriate micropore size, and excellent electrical conductivity is desirable for supercapacitor applications. Herein, porous graphitic carbon sheets (CS) grafted on cellulose fibers (CFs) were fabricated by carbonization of glucose and CFs with the aid of a green activating–graphitizing agent K3 [Fe(C2 O4 )3 ]. In addition to having a sheet-like structure and good electrical conductivity, the as-obtained sample also has a large specific surface area (1515.6 m 2 g −1 ) and a high content of ion-accessible micropores with a size of 0.68 nm, which is optimum for the double layer formation in aqueous electrolyte. Benefiting from the multiple synergistic effects of these features, the sample exhibits a high specific capacitance of 313.0 F g −1 at 1 A g −1 and 240.5 F g −1 at 30 A g −1 in 6 M KOH, revealing an excellent rate capability. In addition, it has a superb cycling stability with 100.2% capacitance retention after 10 000 cycles. Furthermore, the assembled symmetric supercapacitor displays a remarkable energy density of 21.5 W h kg −1 at a power density of 456.5 W kg −1 in Na2 SO4 electrolyte. This work paves a new way to design a novel architectural carbon material linking graphitic CS with optimal micropores for supercapacitor application.